2011
DOI: 10.1159/000330029
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol Isomers Modulate Platelet-Activating Factor Synthesis and Receptor Signaling in Human Bronchial Smooth Muscle Cells

Abstract: Background: Racemic albuterol is a 50:50 mixture of the (R)- and (S)-enantiomers of albuterol. Its clinical efficacy resides in the (R)-enantiomer (levalbuterol). Studies have shown that (S)-albuterol induces human bronchial smooth muscle cell (HBSMC) proliferation via a pathway linked to platelet-activating factor (PAF), but the underlying mechanism by which (S)-albuterol augments PAF effects is not clear. In this study, we compared effect of levalbuterol and (S)-albuterol on PAF receptor (PAFr)-mediated sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
8
0
1
Order By: Relevance
“…TLC bands of the C-14-choline-PAF were scraped off, re-extracted and further purified by high-performance liquid chromatography, as we had reported previously, 9 and quantified by scintillation spectrometry with tritium and carbon-14 windows (Beckman LS 6500). Functional assessment of the purified radiolabeled PAF synthesized from the perinatal lamb lung membrane proteins was tested for bioactivity by the serotonin release method 25 with modifications, as we had recently reported, 26 and then normalized to tissue weight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TLC bands of the C-14-choline-PAF were scraped off, re-extracted and further purified by high-performance liquid chromatography, as we had reported previously, 9 and quantified by scintillation spectrometry with tritium and carbon-14 windows (Beckman LS 6500). Functional assessment of the purified radiolabeled PAF synthesized from the perinatal lamb lung membrane proteins was tested for bioactivity by the serotonin release method 25 with modifications, as we had recently reported, 26 and then normalized to tissue weight.…”
Section: Methodsmentioning
confidence: 99%
“…Functional assessment of the purified radiolabeled PAF synthesized from the perinatal lamb lung membrane proteins was tested for bioactivity by the serotonin release method 25 with modifications, as we had recently reported, 26 and then normalized to tissue weight.…”
Section: Paf In Perinatal Lungs 459mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PAF has a proposed role in airway remodeling including specific effects on smooth muscle proliferation. A provocative recent report indicated that short acting beta 2 agonist (SABA) bronchodilators induce PAF release, possibly contributing to long-term airway inflammation and smooth muscle changes [21]. …”
Section: Platelet-activating Factormentioning
confidence: 99%
“…Позднее упомянутой группой исследователей установлено, что S-сальбутамол может время-зависимо увеличивать связывание PAF с рецептором, коррелирующее с выбросом инозитолтрифосфата, в то время как левосальбутамол и рацемат не оказывают значимых эффектов. Более того, S-сальбутамол интенсифицирует синтез PAF и подавляет его катаболизм (Bae et al, 2012). PAF является важнейшим провоспалительным липидным медиатором, активно вовлекающимся в процессы развития аллергии и воспаления в легких (Roth et al, 1996;Honda et al, 2002).…”
Section: дополнительные благоприятные эффекты β 2 -агонистовunclassified